Functional Vision Screening of Older Adults in Nursing Homes: A Study from Galicia (Northwest Spain). (March 2018) - Sánchez, M. Covadonga Vázquez; Prieto, Luz M. Gigirey; Del-Oro-Sáez, Carlos P.; Piñeiro-Ces, Antonio; Crego, Manuel Gandoy
Introduction: The purpose of this study was to determine the functional vision of a sample of older adults living in nursing homes in Galicia in northwestern Spain. The study is aimed at raising the awareness of clinicians, as well as researchers working in the field of vision and the Spanish Social and Equality Services, regarding the need to develop visual screening protocols in nursing homes, which are currently lacking in Spain (Ministry of Health, Social Services and Equality, n.d.). Methods: Presenting visual acuity (visual acuity with current eyeglasses or contact lenses, if worn) was assessed to determine the functional vision of a sample of older adults living in nursing homes. We tested monocular and binocular high-contrast visual acuity using the directional-E screening test (3.70 scale) for distance vision, and the Rosenbaum near vision chart for near acuity. Visual impairment (distance and near vision) was defined as a binocular presenting visual acuity of less than 6/18 (20/63). Results: The prevalence of visual impairment for distance and near vision reached 23.1% and 16.4%, respectively. We did not find any significant differences in the mean values of presenting visual acuity (far and near vision) between genders. The prevalence of visual impairment for distance vision increased with age (p < 0.01), reaching 25.8% among senior citizens between 80 and 89 years of age, and 50% in the case of nonagenarians. Nevertheless, we did not find any association between age and functional near vision (p > 0.05). Discussion: The findings confirm the high prevalence of visual impairment among this population group. Many of the residents we examined have a level of vision that affects their typical daily activities and quality of life, so it is urgent to develop standard visual screening protocols in nursing homes. Implications for practitioners: Developing visual screening programs in nursing homes would allow for the early detection of visual impairment and help other professionals working in nursing homes—especially clinicians, nurses, and caregivers—to optimize the care of the residents.